Visualization of Real-World 3D Reconstructed Objects with Real-Time Ray Tracing on Ampere Architecture Graphic Processing Unit - Nur Hikmah; Moch Fachri; Risanto Darmawan (Institute of Computer Science (IOCS), 2021)
3D models from the reconstruction of real-world objects have photorealistic details. This realistic detail in the visualization needs to be supported by a visualization environment that is able to represent realistic real-world conditions. However, the environmental light information on the reconstructed 3D object was lost in the reconstruction process. This is because the light obtained from scanned real-world objects for reconstruction can reduce the accuracy of the reconstruction results. This inaccuracy is caused by alterations in the light reflected from the captured object, causing the texture of the object difficult to reconstruct. In the visualization of the scanned object, the light that appears on the object is reformed virtually through ray tracing. This research utilizes the RT core technology on the Ampere graphics processor architecture introduced by Nvidia. With this technology, the ray tracing process can be carried out in real-time, enabling realistic and dynamic visualization. In this study, an application that is able to perform 3D visualization will be made by utilizing real-time ray tracing with an RT core on the graphics processing unit of the Ampere architecture. This application is able to blend virtual environments and 3D models that are reconstructed from the results of scanning real-world objects. We will demonstrate that this application can later become a 3D visualization solution for models from the reconstruction of real-world objects.